2017
DOI: 10.5897/ajmr2017.8571
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological quality of drinking water from source to point of use among rural communities of Farta Woreda in North West, Ethiopia

Abstract: Access to safe water is a universal need. However, many of the world's population lack access to adequate and safe water. Consumption of contaminated water with viruses, bacteria and parasites causes health risk to the public and the situation is serious in rural areas. So this study is aimed at assessing the bacteriological quality of drinking water at source and point of use among rural Communities of Farta Woreda, North Western, Ethiopia. A descriptive cross sectional study was conducted in March 2014 in 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
(8 reference statements)
4
2
1
Order By: Relevance
“…Probably this holds true for some deep multilayered aquifers where the geology does not make it chemically unsafe and is deep enough for most bacteria to live in or sealed top-bottom. This explains the results of the groundwater biological quality in Abuja FCT, those of [28] in Kaduna [29] in Jigawa and [30]…”
Section: Total Bacterial Densitysupporting
confidence: 61%
“…Probably this holds true for some deep multilayered aquifers where the geology does not make it chemically unsafe and is deep enough for most bacteria to live in or sealed top-bottom. This explains the results of the groundwater biological quality in Abuja FCT, those of [28] in Kaduna [29] in Jigawa and [30]…”
Section: Total Bacterial Densitysupporting
confidence: 61%
“…is finding is agreed with the sample from store at Farta woreda, which showed 100% household storage samples were contaminated with E. coli [14,20]; a similar study conducted at Ghana Temale Metropolis found that 83% of household samples were positive for E. coli [11], and this finding was in compliance with the study conducted at Kolladiba town of Ethiopia, which showed that 32.5% water samples from household storage containers were found to be positive for faecal coliforms [17]. Similarly, a study conducted in Bona woreda of southern Ethiopia and Jimma zone of southwest Ethiopia showed that majority of water samples taken from household storage containers were not in compliance with the WHO guideline value of 0 CFU/ 100 ml [12,21,22].…”
Section: Discussionsupporting
confidence: 87%
“…e current study indicates that protected hand-dug wells and shallow wells had significantly more E. coli (60% of tested samples) as compared to protected springs (25% of tested samples). e same study held in Northwest Farta woreda, Amhara region, Ethiopia, showed 83.3% of sample International Journal of Microbiology springs and 91.7% protected wells were positive for E. coli [14]. is finding is agreed with the study conducted at Fogera and Mecha woredas of North Gonder, Ethiopia, which showed 73.77% of community water source samples were contaminated with E. coli.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations